2019
DOI: 10.5194/amt-12-4439-2019
|View full text |Cite
|
Sign up to set email alerts
|

An IBBCEAS system for atmospheric measurements of glyoxal and methylglyoxal in the presence of high NO<sub>2</sub> concentrations

Abstract: Abstract. A system based on incoherent broadband cavity-enhanced absorption spectroscopy (IBBCEAS) has been developed for simultaneous measurement of nitrogen dioxide (NO2), glyoxal (GLY), and methylglyoxal (MGLY). In this system, the measured light absorption at around 460 nm is spectrally resolved. The concentration of absorbers is determined from a multicomponent fit. At an integration time of 100 s, the measurement sensitivity (2σ) for NO2, GLY, and MGLY is 18, 30, and 100 ppt, respectively. The measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The ∆NO 2, CAPS day/night time variations are stronger during the first part of the campaign that is impacted by higher ozone mixing ratios, which is a sign for stronger photo-chemistry. Previous studies have shown that dialdehydes absorb light in the wavelength range used by the CAPS instrument to detect NO 2 [48,49]. The dominant ones in the troposphere, glyoxal and methyl-glyoxal, are produced by photo-chemical oxidation of hydrocarbons (mostly isoprene [50]), which is the same mechanism that drives the formation of ozone during daytime.…”
Section: Ambient Air Measurementsmentioning
confidence: 99%
“…The ∆NO 2, CAPS day/night time variations are stronger during the first part of the campaign that is impacted by higher ozone mixing ratios, which is a sign for stronger photo-chemistry. Previous studies have shown that dialdehydes absorb light in the wavelength range used by the CAPS instrument to detect NO 2 [48,49]. The dominant ones in the troposphere, glyoxal and methyl-glyoxal, are produced by photo-chemical oxidation of hydrocarbons (mostly isoprene [50]), which is the same mechanism that drives the formation of ozone during daytime.…”
Section: Ambient Air Measurementsmentioning
confidence: 99%
“…The CEAS system has been described in detail in previous literature (Duan et al, 2018;Fiedler et al, 2003;Gherman et al, 2008;Jordan and Osthoff, 2020;Jordan et al, 2019;Langridge et al, 2006;Liang et al, 2019;Liu et al, 2019;Min et al, 2016;Tang et al, 2020;Ventrillard-Courtillot et al, 2010;Wang et al, 2017a;Yi et al, 2016), so there is a brief introduction to the principle of the instrument. NO2 molecules have a specific absorption structure in the wavelength range of 400-500 nm (Fig.…”
Section: Instrumentation Of Td-ceasmentioning
confidence: 99%
“…The fitting shift is constrained within ±0.2 nm. Glyoxal has strong absorption in the same optical window (Liu et al, 2019;Min et al, 2016;Thalman et al, 2015;Thalman and Volkamer, 2010;Washenfelder et al, 2008), but here we do not take into consideration in spectrum fitting. Fig.…”
Section: Spectral Fittingmentioning
confidence: 99%
“…in min) is challenging and puts stringent constraints on the instrument sensitivity, time response, energy consumption and compactness. Among the various techniques that have so far been developed, chemiluminescence detection (CLD) (Maeda et al, 1980;Ryerson et al, 2000), long-path differential optical absorption spectroscopy (LP-DOAS) (Lee et al, 2005(Lee et al, , 2008Pikelnaya et al, 2007) and multi-axis differential optical absorption spectroscopy (MAX-DOAS) (Platt and Perner, 1980;Sinreich et al, 2007;Wagner et al, 2010) have been used to detect nitrogen species and halogen oxides. The CLD technique, using the chemiluminescence reaction occurring between O 3 and NO after the reduction of NO 2 into NO, is widely used for air quality measurements with sensitivities better than 100 ppt (Ryerson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%